Regional covariance of white matter hyperintensity volume patterns associated with hippocampal volume in healthy aging - Van Etten, Emily J.; Bharadwaj, Pradyumna K.; Grilli, Matthew D.; Raichlen, David A.; Hishaw, Georg A.; Huentelman, Matthew J.; Trouard, Theodore P.; Alexander, Gene E. (Frontiers in Aging Neuroscience, 2024)
Hippocampal volume is particularly sensitive to the accumulation of total brain white matter hyperintensity volume (WMH) in aging, but how the regional distribution of WMH volume differentially impacts the hippocampus has been less studied. In a cohort of 194 healthy older adults ages 50-89, we used a multivariate statistical method, the Scaled Subprofile Model (SSM; Alexander & Moeller, 1994), to 1) identify patterns of regional WMH differences related to left and right hippocampal volumes, 2) examine associations between the multimodal neuroimaging covariance patterns and demographic characteristics, and 3) investigate the relation of the patterns to subjective and objective memory in healthy aging. We established network covariance patterns of regional WMH volume differences associated with greater left and right hippocampal volumes, which were characterized by reductions in left temporal and right parietal WMH volumes and relative increases in bilateral occipital WMH volumes. Additionally, we observed lower expression of these hippocampal-related regional WMH patterns were significantly associated with increasing age and greater subjective memory complaints, but not objective memory performance in this healthy older adult cohort. Our findings indicate that, in cognitively healthy older adults, left and right hippocampal volume reductions were associated with differences in the regional distribution of WMH volumes, which were exacerbated by advancing age and related to greater subjective memory complaints. Multivariate network analyses, like SSM, may help elucidate important early effects of regional WMH volume on brain and cognitive aging in healthy older adults.